Corporate social responsibility and Islamic social finance impact on banking sustainability post-COVID-19 pandemic - Madah Marzuki, Marziana; Nik Abdul Majid, Wan Zurina; Rosman, Romzie (Elsevier, 2023)
This study aims to explore Corporate Social Responsibility (CSR) and Islamic Social Finance activities in Bank Pembangunan Malaysia Berhad (BPMB) as one of the Development of Financial Institutions (DFIs) in Malaysia and their impact on sustainability post-coronavirus disease (COVID-19) (2021–2023). A semi-structured interview was conducted among the top management and employees of BPMB. Resultantly, the bank has aligned its Islamic Social Finance and CSR activities with the third Sustainable Development Goal (SDG). Nevertheless, the impact on banking sustainability post-pandemic remains uncertain as efforts towards SDG remain at the preliminary stage. Conclusively, Islamic Social Finance and CSR are critical to enhance banking sustainability. This study provide insight to other DFIs in understanding the role of Corporate Social Responsibility (CSR) and Islamic Social Finance activities in achieving sustainability post pandemic.